Deixis in the Speakers’ Speech in the Program Mata Najwa Episode Why We Need Comics and its Implication for Learning Indonesian Language in Senior High School - Hasanah, Hemas Virginia Uswatun; Sumarti, Sumarti; Agustina, Eka Sofia (Universitas Lampung, 2024)
The problem in this research is how deixis in the speech of speakers in the program Mata Najwa episode of Why We Need Comics and its implication to Indonesian language learning in senior high school. This research uses a qualitative descriptive design. The data source of this research is the video of Mata Najwa episode Why We Need Comics with a duration of 51 minutes 24 seconds. Data collection uses the technique of Simak Libat Bebas Cakap (SLBC) and note technique. The data analysis technique used the commensurate method with the Pilah Unsur Penentu (PUP) technique followed by the Hubung Banding Menyamakan (HBS) technique. The results show that the deixis contained in the speech of the speakers in the program Mata Najwa episode of Why We Need Comics, includes (a) person deixis which is classified into three, namely first person (I, me, I, my, and us), second person (you and you), and third person (his/its, he, and they). Place deixis (there, there, this, and that). Time deixis which is classified into three, namely the past (yesterday, that time, and long ago), the present (now), and the future (tomorrow). Discourse deixis (that, this, there and there). Social deixis (sister, brother, sis/bro, and mr./sir). This deixis research is applied to Indonesian language learning in senior high school class X as complementary material for learning anecdotal text on Learning Objective (TP) 10.6 students write their ideas logically, critically, and creatively in the form of anecdotal text based on the media presented by paying attention to the right structure and appropriate language rules. Permasalahan dalam penelitian ini adalah bagaimana deiksis tuturan narasumber dalam acara Mata Najwa episode Mengapa Kita Membutuhkan Komik dan implikasinya terhadap pembelajaran bahasa Indonesia di SMA. Penelitian ini menggunakan desain deskriptif kualitatif. Sumber data penelitian ini adalah video Mata Najwa episode Why We Need Comics yang berdurasi 51 menit 24 detik. Pengumpulan data menggunakan teknik Simak Bebas Cakap (SLBC) dan teknik catat. Teknik analisis data menggunakan metode sepadan dengan teknik Pilah Elemen Penentu (PUP) yang dilanjutkan dengan teknik Hubung Banding Meyamakan (HBS). Hasil penelitian menunjukkan bahwa deiksis yang terkandung dalam tuturan para narasumber dalam acara Mata Najwa episode Mengapa Kita Membutuhkan Komik, meliputi (a) deiksis persona yang diklasifikasikan menjadi tiga yaitu orang pertama (gua, aku, saya, -ku, dan kita), orang kedua (Anda dan lu), dan orang ketiga (-nya, dia, dan mereka). Deiksis tempat (sana, situ, ini, dan itu). Deiksis waktu yang diklasifikasikan menjadi tiga, yaitu masa lalu (kemarin, waktu itu, dan dulu), masa kini (sekarang), dan masa depan (besok). Deiksis wacana (itu, ini, sana, dan situ). Deiksis sosial (mbak, bang, kak, dan pak). Penelitian deiksis ini diterapkan pada pembelajaran bahasa Indonesia di SMA kelas X sebagai materi pelengkap pembelajaran teks anekdot pada Tujuan Pembelajaran (TP) 10.6 siswa menuliskan gagasannya secara logis, kritis, dan kreatif dalam bentuk teks anekdot berdasarkan media yang disajikan. dengan memperhatikan struktur yang benar dan kaidah bahasa yang tepat. Keywords: Deixis, Mata Najwa, Implication, Indonesian Language Learning